1973
DOI: 10.1084/jem.138.5.1213
|View full text |Cite
|
Sign up to set email alerts
|

Function of Macrophages in Antigen Recognition by Guinea Pig T Lymphocytes

Abstract: Recent studies indicate that histocompatibillty-linked immune response (It) 1 genes, are expressed on thymus-derived (T) lymphocytes. In the mouse, the genetically controlled difference in the IgG antibody response between high and low responders immunized with branched-chain amino acid polymers is lost in thymus-deprived mice (1). In guinea pigs, the initiation of functions thougtrt to be regulated by T lymphocytes (delayed cutaneous hypersensitivity, antigen-induced lymphocyte proliferation in vitro, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
97
0
1

Year Published

1974
1974
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(103 citation statements)
references
References 11 publications
5
97
0
1
Order By: Relevance
“…As stressed above, functional studies have shown that macrophages and lymphocytes cooperate in the immune response (9,(11)(12)(13)(14)(15)(16)(17)(18) and some of the evidence indicates that the cooperation requires physical contact between the two cells. The clusters described here may provide a microenvironment necessary for macrophage-lymphocyte cooperation mediated by surface contact and/or soluble factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As stressed above, functional studies have shown that macrophages and lymphocytes cooperate in the immune response (9,(11)(12)(13)(14)(15)(16)(17)(18) and some of the evidence indicates that the cooperation requires physical contact between the two cells. The clusters described here may provide a microenvironment necessary for macrophage-lymphocyte cooperation mediated by surface contact and/or soluble factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, addition of macrophages pulsed with purified protein derivative of tuberculin (PPD) by brief exposure in vitro induces blast transformation in purified populations of syngeneic immune lymphocytes from guinea pig (11)(12)(13)(14), rabbit (9,15), and man (16,17). Some data suggest that this macrophage-lymphocyte cooperation requires physical interaction between the two cells (9,15,16) during which the macrophage presents molecules of surface-bound antigen to the lymphocyte (14)(15)(16)(17)(18). This investigation was supported by Statens L~egevidenskabelige Forskningsr~d, grants 512-1116 and 512-2685.…”
mentioning
confidence: 99%
“…If the C! structures were not allelically excluded, one could still explain the existence of independent sets of F~ cells which recognize antigen-pulsed macrophages from each parent by postulating a stable association between antigen receptor and CI structure on the T-lymphocyte membrane (15) and by requiring that, on any individual T lymphocyte, the allelic forms of CI structures were associated with distinct antigen receptors. Thus, (2 × 13)Fs cells which recognize OVA-pulsed 2 PECs would do so because they possessed a receptor for OVA closely associated with the strain 2 CI structure.…”
Section: Role Of Ia Antigens Tn Negative Selectmn By Anttgen-pulsed Pmentioning
confidence: 99%
“…The histocompatibility restriction in the interaction of primed T lymphocytes with antigen-pulsed PECs or with B lymphocytes has previously been interpreted in terms of self-recogultion by cellular interaction (CI) structures borne by the interacting cell types (15,16). This hypothesis held that activation of primed T lymphocytes by antigen-pulsed PECs requires that the T lymphocyte recognize antigen by virtue of its specific antigenbinding receptor and that PEC and T lymphocyte each express CI structures, encoded within the I region of the MHC, which are capable of mutual recognition.…”
Section: Role Of Ia Antigens Tn Negative Selectmn By Anttgen-pulsed Pmentioning
confidence: 99%
“…Previous studies in the guinea pig (1,2) have demonstrated the requirement for genetic identity at the MHC in order for peritoneal exudate cells to present antigen effectively to primed T lymphocytes. Experiments designed to test whether similar genetic restrictions applied to antigen presentation by murine spleen cells are shown in Table I.…”
Section: Antigen Presentation By Syngeneic Semisyngeneic or Allogenmentioning
confidence: 99%